Agro-based entrepreneurship and food security in Nigeria: Panacea for sustainable development (West African Journal on Sustainable Development, 2024)
Government age long dependency in oil and gas as its primary source of revenue has unintended negative consequence in Agro based industries and food security in Nigeria. Despite Government neglect to support agro-based entrepreneurship, enterprises in agriculture possess value chains with an intriguing potential to create sustainable economic development for Nigeria. This emphasizes the need for development partners to adopt already existing SME programmes and ideas to meet the needs of farmers in order to add value to their agricultural products, and invest in new interventions targeted at value addition for rural development and increased agricultural productivity for small scale farmers. Hence, the present study explored agro-based entrepreneurship and food security in Nigeria. Agro-based entrepreneurship has encouraged diversification into non-traditional agricultural products and value addition to reduce vulnerability and enhanced food security and poverty reduction. The study examined the development of Entrepreneurship in Nigeria, Identified various agro-based businesses that can thrive in Nigeria, emphasized the role of agro-based entrepreneurship in food security, national economy and sustainable development. Furthermore, the study examined the guiding theory the assumptions of the study and identified challenges that young entrepreneurs face in Nigeria with an insight into the role of Government in ensuring sustainable food security in Nigeria. It is recommended that agro-based entrepreneurs be encouraged to enhance their skills so as to access appropriate information using ICT tools which will provide the necessary information on weather forecast patterns, input prices, projected market prices, government incentives, and agricultural-related policies and programmess. The study further recommended that Government should support rising agro-based entrepreneurs with sponsorships of trainings on agricultural entrepreneurship, innovations and technologies, which are essential in meeting up with the current trends in agro based industries.
Keywords: Entrepreneurship; Food Security; Sustainable Development